UPDKS CONTROL MANAGEMENT SYSTEM ENVIRONMENTAL CONSCIOUSNES IN PALM OIL PRODUCING CROPS (CASE STUDY: ADOLINA, PT. PERKEBUNAN NUSANTARA IV): SISTEM MANAJEMEN PENGENDALIAN UPDKS YANG BERWAWASAN LINGKUNGAN PADA TANAMAN MENGHASILKAN KELAPA SAWIT (STUDI KASUS : KEBUN ADOLINA PT. PERKEBUNAN NUSANTARA IV) - Tuty Ningsih, S.P., M.P; Fadli Akbar Lubis; Ahmad Habibi; Naldo Febrianto P; Khairunisa Rahmawanti (Agro Estate, 2024)
UPDKS control management is one way to control UPDKS so that palm oil production potential remains optimal. The research was conducted at PT. Regional II Adolina Gardens. Perkebunan Nusantara IV Regional II in January – July 2022. The research method used is a qualitative descriptive method, namely a method that describes the management system for controlling Oil Palm Leaf Eating Caterpillars (UPDKS) with an environmental perspective. The results of the research show that the implementation of UPDKS pest control practices in Adolina Gardens is in accordance with the SOP which refers to the early warning system, with the provisions that if the economic threshold for bagworms is more than 3 caterpillars per tree and fireworms are more than 5 caterpillars per tree then control will be carried out